Influence of water quality on nutritional and sensory characteristics of green tea infusion. Issue 5 (11th January 2017) - Murugesh, C. S.; Manoj, J. B.; Haware, D. J.; Ravi, R.; Subramanian, R.
Abstract: Impact of water quality on the nutritional and sensory characteristics of green tea infusion was studied. The total soluble tea solids, catechins andl ‐theanine concentrations were significantly higher in infusions prepared from water having lower total dissolved solids (TDS, 0.59 to 13.0 ppm), conductivity (1.12 to 26.20 µS), and pH (6.04 to 6.90). The difference in extractability was explained using the mass transfer equation dN T / dt  =  k L A s ( C Te  −  C TL ); where dN T / dt ‐mass transfer rate, k L ‐mass transfer coefficient, A s ‐surface area, C Te ‐equilibrium concentration, and C TL ‐concentration in bulk liquid. The major catechins reduced (∼84–93%) in the infusions prepared from water with higher TDS (315 to 338 ppm), conductivity (630 to 679 µS), and pH (7.65 to 8.05), accompanied with undesirable color changes during storage following the first‐order kinetics. Tea cream and turbidity were much higher with water having higher calcium concentration (51.60 mg/L). The study recommended water with low TDS, conductivity and pH for hot‐infusions and beverages. Practical applications: The study was initiated to select a suitable type of water for the preparation of green tea infusion and ready‐to‐drink (RTD) beverages. For infusion, the extractability of the nutrients as well as the sensory characteristics are important. Accordingly, ultra‐pure (UP), packaged drinking (PD), or reverse osmosis (RO) water may be used for the preparation. But, in the case of RTD beverages, the physical stability and visual appearance are also equally important for consumer acceptance, as they are held in storage and distribution before being consumed. Furthermore, the results indicated that stability of catechins need to be considered as a parameter for the selection of water. Even though UP, PD, or RO meets all these criteria, economic considerations propel RO water for RTD production. Thus the inferences obtained from this scientific study has practical relevance in the selection of appropriate quality of water for the preparation of green tea beverages.